‘Fully Diagnosed, Fully Stabilised and Fully Treated’: Succeeding in a Claim for a Disability Support Pension in Australia for Endometriosis and Chronic Pelvic Pain - Karena Viglianti (Bond Law Review, 2023)
In 2019, Ms Natasha Thomson won an application for a disability support pension (DSP) under the Social Security Act 1991 (Cth) before the Australian Administrative Appeals Tribunal (AAT). Ms Thomson was taken to the AAT by the Department of Social Security when it appealed a decision of the AAT’s Social Services and Child Support Division. Ms Thomson is the only applicant with chronic pelvic pain and likely endometriosis that has succeeded in her claim for a DSP before the Tribunal since 2005. Endometriosis is an inﬂammatory condition characterised by endometrial-like tissue growing outside the uterus, which can result in pain and adhesions. It commonly grows on the pelvic organs and peritoneum but has been found in other parts of the body, such as the lungs, diaphragm, kidney and navel. There is no cure at present. Long-term management is required using medical and/or surgical treatment, both of which focus on alleviating symptoms. In this article, I consider the AAT’s determinations and set out what applicants, their legal representatives and their treating doctors can learn from the cases on applicants for a DSP with endometriosis and chronic pelvic pain.